2021
DOI: 10.1001/jamaoto.2020.5286
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Diffuse Type 2 Dominant or Eosinophilic Chronic Rhinosinusitis With Corticosteroid Irrigation After Surgical Neosinus Cavity Formation

Abstract: IMPORTANCE Eosinophilic chronic rhinosinusitis (eCRS), contemporarily classified as diffuse type 2 dominant chronic rhinosinusitis (CRS), is characterized by eosinophil-dominant mucosal inflammation. Contemporary management of eCRS as an inflammatory airway condition is multimodal with corticosteroid irrigations after the surgical creation of a neosinus cavity.OBJECTIVES To assess long-term treatment outcomes in patients with primary diffuse type 2 CRS or eCRS receiving multimodal treatment. DESIGN, SETTING, A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 51 publications
1
19
0
Order By: Relevance
“…ECRS is associated with a high postoperative recurrence rate of 7.2%-20% at 12 months after ESS. 3,11,12 Although biologics have become popular as a treatment for recurrence, systemic steroids are currently often administered first for subjective exacerbation of symptoms that occur postoperatively. Steroid use is a treatment for postoperative recurrence and may also influence subsequent treatment strategies, including the indication for biologic agents.…”
Section: Discussionmentioning
confidence: 99%
“…ECRS is associated with a high postoperative recurrence rate of 7.2%-20% at 12 months after ESS. 3,11,12 Although biologics have become popular as a treatment for recurrence, systemic steroids are currently often administered first for subjective exacerbation of symptoms that occur postoperatively. Steroid use is a treatment for postoperative recurrence and may also influence subsequent treatment strategies, including the indication for biologic agents.…”
Section: Discussionmentioning
confidence: 99%
“…Patients underwent endoscopic sinus surgery as part of management of their eCRS. 16 This study was limited to patients with disease sub-optimally controlled clinically and symptomatically to warrant operative management. In patients with eCRS, multimodal therapy with surgery, topical medication irrigations and systemic medications (corticosteroids, biologics) has been shown to be successful in most patients to control disease and reduce symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with eCRS, multimodal therapy with surgery, topical medication irrigations and systemic medications (corticosteroids, biologics) has been shown to be successful in most patients to control disease and reduce symptoms. 16 The objective for surgery was to provide a wide-open suitable cavity to maximise the postoperative delivery of corticosteroids to the sinonasal mucosa. Operations included revision polypectomy in patients who had recurrent disease/polyposis despite a previously adequately widened sinonasal cavity, to more extensive sinus surgery including Lothrop procedure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10,11 Some studies have reported good results using corticosteroid irrigation, but the irrigation method causes discomfort to patients, and corticosteroids are inconvenient to carry. 12 Therefore, improving the existing drug delivery method for nasal spray hormones and achieving the precise application of glucocorticoids to local sinus lesions have become a focus of CRS treatment research.…”
Section: Introductionmentioning
confidence: 99%